2011
DOI: 10.1002/pssc.201001194
|View full text |Cite
|
Sign up to set email alerts
|

Differential photoacoustic cell to study the wetting process during porous silicon formation

Abstract: This paper shows the in‐situ study of the wetting process in Silicon during anodization process using an electrochemical Differential photoacoustic Cell (DPC). The Photoacoustic amplitude and phase signals were obtained for samples in air, ethanol, ethanol/HF and finally air. According to these results ethanol is responsible for a mechanical contact reducing the superficial tension and ethanol/HF produce the removing of the SiOx and SiO2species on the Silicon surface. It was found that the DPC is a powerful te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…The data reported by Gutierrez et al and Espinosa-Arbeláes et al showed an oscillatory character for the amplitude and phase signals of the photoacoustic signal. 6,7 This shows clearly that the photoacoustic signal depends on various parameters: substrate impurity concentration, current density, and the hydrofluoric acid (HF)/surfactant ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The data reported by Gutierrez et al and Espinosa-Arbeláes et al showed an oscillatory character for the amplitude and phase signals of the photoacoustic signal. 6,7 This shows clearly that the photoacoustic signal depends on various parameters: substrate impurity concentration, current density, and the hydrofluoric acid (HF)/surfactant ratio.…”
Section: Introductionmentioning
confidence: 99%
“…PA has been used to study kinetic processes, thermal and electronic properties of semiconductor materials. [10][11][12][13] Therefore, it is expected that the PA technique could be able to detect in situ the chemical reaction and the changes in the optical properties during the PS formation.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the electrolyte is also important. Commonly, the electrolyte base is an aqueous HF (37-40%) added with a surfactant (e.g., ethanol or glycerol) to decrease the surface tension, which results in a better wettability [21]. The temperature of the electrolyte reservoir and the HF/surfactant ratio are the parameters that strongly influence the roughness of the PSi films [41].…”
Section: Porous Silicon Formationmentioning
confidence: 99%
“…The main techniques reported to study the in situ formation of PSi by electrochemical etching in hydrofluoric acid(HF) media are: in situ Fourier transform infrared spectrometry (FTIR) [10,11], optical interferometry [12][13][14][15][16][17] optical scattering [19,20], and photoacoustics [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation